Application of Pancasila Values in Against the Radicalism of Indonesia - Yuniar Megalia; Dimas Rangga Ahimsa (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Indonesia is a country that has diverse religions, ethnicities and cultures. Based on the Pancasila, making this country have a strong national ideology that is expected to embrace all the differences in this country. In the Pancasila which has a long history, which finally by the nation's father (Bung Karno) sparked five principles as the basis of the Indonesian state namely Indonesian nationality, internationalism or humanity, unity and unity, social welfare, and the Supreme God who later called the Pancasila was born on June 1, 1945. The basic value of the Pancasila must be embedded in every human being so that it is not possible for other ideologies to replace the figure of Pancasila as a national identity. It is undeniable that Bung Karno's wild thinking of nationalist, religious and communist ideals made humans have wild thoughts that would make him a radical without remembering Pancasila identity which has become a philosophy of gronslag in this country. So it is very important for everyone to apply Pancasila values so that radical thinking does not arise that tries to deviate from the noble values of Pancasila.